GE14 : the urban voting pattern in P172 Kota Kinabalu and P186 Sandakan, Sabah - Anantha Raman Govindasamy,; Yew, Meng Lai (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article examines two urban Chinese dominated parliamentary seats in Sabah namely P172 Kota Kinabalu and P182 Sandakan. It will also study the political development within the state assembly seats under these two parliamentary seats. Specifically, the article will explore the candidates and the main contested issues, the voting pattern and the results of the recently concluded 14th Malaysian general election. By largely utilising fieldwork observation during the election campaign, this article argues that Pakatan Harapan’s huge victory in these parliamentary and state assembly seats are mainly because of the close working relationship with Parti Warisan Sabah, which significantly helped the DAP and PKR candidates to make inroad into Muslim-Bumiputra dominated areas in these Chinese majority parliamentary seats in Sabah.